Analisis Kebutuhan E-Module Berbasis Project Based Learning pada Materi Pokok Gelombang Bunyi Kelas XI SMA - Rahimah Rahimah; Hadma Yuliani; Nur Inayah Syar (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
E-module is part of teaching materials that can be applied by students in the learning process. This study aims to 1) look at the teaching materials used by students; 2) knowing the obstacles faced by students in the learning process to understand the physics material; 3) analyze the needs of students for Project Based Learning (PjBL) based E-modules on sound wave material for class XI SMA. This type of research uses descriptive qualitative in the form of interviews and questionnaires. The data collection technique is to distribute needs questionnaires to class XI students of SMA Muhammadiyah 1 Palangka Raya online in the form of a google form platform via WhatsApp. The results of the research conducted showed that 1) the teaching materials used by students were 14.3% books, 23.8% modules, 28.6% LKS, 14.3% PPT, 28.6% PDF, and 9.5% tutorial video; 2) obstacles faced by students in understanding physics material, namely the lack of understanding of material concepts so that students have difficulty understanding physics formulas and applying them in everyday life; 3) students need teaching materials such as PjBL-based E-modules according to the data obtained, as many as 81% of students agree on the development of PjBL-based E-modules in making it easier for students to understand physics material and apply it in everyday life, especially on sound wave material.